Developing a tissue engineered repair material for treatment of stress urinary incontinence and pelvic organ prolapse—which cell source?. Issue 5 (19th July 2013) - Roman, Sabiniano; Mangera, Altaf; Osman, Nadir I.; Bullock, Anthony J.; Chapple, Christopher R.; MacNeil, Sheila
Abstract Aims Synthetic non‐absorbable meshes are widely used to augment surgical repair of stress urinary incontinence (SUI) and pelvic organ prolapse (POP); however, there is growing concern such meshes are associated with serious complications. This study compares the potential of two autologous cell sources for attachment and extra‐cellular matrix (ECM) production on a biodegradable scaffold to develop tissue engineered repair material (TERM). Methods Human oral fibroblasts (OF) and human adipose‐derived stem cells (ADSC) were isolated and cultured on thermo‐annealed poly‐L‐lactic acid (PLA) scaffolds for two weeks under either unrestrained conditions or restrained (either with or without intermittent stress) conditions. Samples were tested for cell metabolic activity (AlamarBlue® assay), contraction (serial photographs analyzed with image J software), total collagen production (Sirius red assay), and production of ECM components (immunostaining for collagen I, III, and elastin; and scanning electron microscopy) and biomechanical properties (BOSE tensiometer). Differences were statistically tested using two sample t‐test. Results Both cells showed good attachment and proliferation on scaffolds. Unrestrained scaffolds with ADSC produced more total collagen and a denser homogenous ECM than OF under same conditions. Restrained conditions (both with and without intermittent stress) gave similar total collagen production, but improved elastin production for both cells, particularly OF. The addition of any cell onto scaffolds led to an increase in biomechanical properties of scaffolds compared to unseeded scaffolds. Conclusions OF and ADSC both appear to be suitable cell types to combine with biodegradable scaffolds, in the development of a TERM for the treatment of SUI and POP. Neurourol. Urodynam. 33:531–537, 2014. © 2013 Wiley Periodicals, Inc.